2020
DOI: 10.3390/ma13071511
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Combination of Strength and Electrical Conductivity of Al-Mg-Si Alloy Processed by ECAP with Two-Step Temperature

Abstract: The mechanical properties and electrical conductivity of 6063 aluminum alloy subjected to equal-channel angular press (ECAP) at room temperature (RT), 200 °C, and two-step temperature schedule (TST) have been investigated in this study. The TST refers to one pass at 200 °C followed by further successive pressing at RT. It is shown that this method is effective in obtaining the combination of high strength and electrical conductivity. After two passes, the higher strength can be achieved in TST condition (328 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…20,28) Another direction in the field is related to optimization of the SPD processing temperature leading to utilizing advantages of both dynamic and static ageing. 29) These studies logically led to a step up in producing UFG Al 6xxx semi-products in the form of wires by combining enhanced SPD (the continuous ECAP-C scheme, for example) with traditional routes such as drawing. 3032) In addition to the improved static strength/ conductivity ratio these wires demonstrated better fatigue properties 2,32,33) as compared to traditional TMT, which is important for automotive applications where vibrational loads are essential 2) or for the fretting fatigue issue.…”
Section: Age-hardenable Almgsi Alloysmentioning
confidence: 99%
“…20,28) Another direction in the field is related to optimization of the SPD processing temperature leading to utilizing advantages of both dynamic and static ageing. 29) These studies logically led to a step up in producing UFG Al 6xxx semi-products in the form of wires by combining enhanced SPD (the continuous ECAP-C scheme, for example) with traditional routes such as drawing. 3032) In addition to the improved static strength/ conductivity ratio these wires demonstrated better fatigue properties 2,32,33) as compared to traditional TMT, which is important for automotive applications where vibrational loads are essential 2) or for the fretting fatigue issue.…”
Section: Age-hardenable Almgsi Alloysmentioning
confidence: 99%
“…According to Figure 7, it is worth noting that the conductivity performance of different states for Al-2Fe-xCo alloys are in the following sequence: as-cast < annealing < rolling. It is known that many factors affect the thermal conductivity of alloys, such as alloy composition [2,7,36,37], heat treatment [10,11,38,39], melt treatment [40,41], plastic deformation [1,42], and so on. In our study, compared with the as-cast samples, the thermal conductivities of alloys significantly increase after annealing From Figure 7a, the thermal diffusivity of as-cast specimens first increases from 0.837 cm 2 /s for the Al-2Fe alloy to 0.856 cm 2 /s for Al-2Fe-0.3Co alloy by improving the amplitude of 2.3%, and then gradually decreases with increasing Co content.…”
Section: Conductivity Performance Of Al-2fe-xco Ternary Alloysmentioning
confidence: 99%
“…For the past decade, multiple researchers have tried to simultaneously improve the strength and electrical/thermal conductivity of aluminum alloys with the increasing demand of heat-dissipating equipment, such as heat radiators, 5G communication base stations, and so on [ 1 , 2 , 3 , 4 ]. However, it was reported that thermal conductivity and mechanical properties are contradictory factors in the alloys [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to alloying, various SPD techniques, such as equalchannel angular pressing, [34][35][36][37] high-pressure torsion, [1] and friction stir processing, [38] have been widely investigated for improving the strength and EC of Al-Mg-Si alloys. These techniques can induce ultrafine-grained microstructures with enhanced mechanical performance, but also alter the precipitation behavior, which consequently affects the EC of the alloys.…”
Section: Introductionmentioning
confidence: 99%